Analysis of Managerial Decision Making Based on Cost and Revenue Structure in Riteal Companies - Kholilul Kholik; Sarifah Rista Maulina; Anton Sobirin (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to analyze the effect of cost structure and revenue projections on managerial decision-making processes in the retail sector amid the economic dynamics of 2025. Amidst fluctuations in people's purchasing power and increased operational costs due to minimum wage adjustments and logistics costs, managers are required to optimize profit margins without sacrificing market competitiveness. The methodology used is quantitative descriptive by conducting a Cost-Volume-Profit (CVP) analysis and Break-Even Point evaluation on the research object. The results of the study show that accurate identification of fixed and variable costs enables management to design more flexible and competitive pricing strategies. Key findings indicate that retail companies that adopt real-time sales data integration into their revenue structure are able to make stock and promotion decisions 30% faster than conventional models. This analysis concludes that strengthening the cost structure through operational digitization is crucial for managers to mitigate the risk of losses and ensure business sustainability amid global market uncertainty in 2025.